Pennsylvania Archives. October 14-1756-January 3, 1764 - Hoban, Charles F. (Eighth Series, 1935)
A collection of documents supplementing the companion series known as "Colonial records," which contain the Minutes of the Provincial council, of the Council of safety, and of the Supreme executive council of Pennsylvania.
Keywords: History; Pennsylvania; Periodicals; Periodicals; Pennsylvania; Sources; unidentified

A Study of Double Grades in New Haven City Schools - Knight, E.E. (Journal of Experimental Education, 1938)
Keywords: dept.nhstc